Building Collaboration Between Educational Institutions and Communities Impacting School Management: A Case Study of Guangzhou Vocational College of Technology, Guangzhou Open University, China - Worapongpat, Ntapat (Journal of Education and Learning Reviews, 2025)
Background and Aim: Effective collaboration between schools and communities is increasingly recognized as a cornerstone of quality education, especially in vocational institutions where practical engagement with local stakeholders is essential. However, many institutions still struggle with unclear collaboration models, inadequate tools, and insufficient responsiveness to community needs. This study investigates school-community collaboration in the context of Guangzhou Vocational College of Technology and Guangzhou Open University in China, aiming to identify practical strategies to enhance educational management and long-term community engagement. Materials and Methods: The study surveyed 268 administrators and teachers from 26 affiliated institutions, sampled proportionally from a population of 650 using Krejcie and Morgan’s formula and stratified sampling. A validated questionnaire (IOC = 0.7–1.0) was administered following a pilot test (Cronbach’s Alpha = 0.85). Descriptive statistics (mean, standard deviation) and inferential analyses (Pearson’s correlation and stepwise multiple regression) were employed to examine relationships between community engagement and educational administration. Results: Findings revealed that both the level of school-community collaboration and the quality of educational administration were high. Moreover, significant positive correlations were found between community engagement and educational management (p < .01). Notably, support for school activities was a strong positive predictor, while community services unexpectedly showed a negative association with administrative outcomes. Conclusion: The study highlights the dual impact of community involvement on school management: while support for school-led initiatives strengthens educational administration, unmanaged or resource-intensive community services may hinder institutional performance. These findings underscore the need for balanced, strategic collaboration models tailored to vocational education settings.